Domesticating wild fruit trees - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Ann Degrande of ICRAF in Cameroon tells Martha Chindong how families can benefit from cultivating wild fruit tree species near their homes.